Outcome of liver transplantation for hepatopulmonary syndrome: a Eurotransplant experience. Issue 2 (31st January 2019) - Raevens, Sarah; Rogiers, Xavier; Geerts, Anja; Verhelst, Xavier; Samuel, Undine; van Rosmalen, Marieke; Berlakovich, Gabriela; Delwaide, Jean; Detry, Olivier; Lehner, Frank; Mittler, Jens; Nadalin, Silvio; et al.
Hepatopulmonary syndrome (HPS) is a pulmonary vascular complication of liver disease that affects up to 30% of patients with cirrhosis [1]. Intrapulmonary vascular dilatations and shunts result in gas exchange abnormalities, ranging from elevated alveolar–arterial oxygen gradients with no hypoxaemia to very severe hypoxaemia [1, 2]. Currently, liver transplantation (LT) is the only treatment option [3]. The Model for End-Stage Liver Disease (MELD) is a scoring system for assessing liver disease severity that has been validated to predict the 3-month waiting list mortality and is used by Eurotransplant for prioritising allocation of liver transplants [4]. However, this score poorly predicts overall and post-transplant survival, and does not take into account complications that affect outcomes independent of liver disease severity [5]. Equal overall survival among liver transplantation candidates supports current prioritisation policy for severe hepatopulmonary syndrome http://ow.ly/4SQS30mwOtK